Optimization, validation and application of a high‐throughput 96‐well elution protocol for the quantification of psychoactive substances in influent wastewater. Issue 2 (8th November 2022) - Boogaerts, Tim; Quireyns, Maarten; Maes, Florence; Laimou‐Geraniou, Maria; Van Wichelen, Natan; Heath, Ester; Pussig, Bram; Aertgeerts, Bert; Covaci, Adrian; van Nuijs, Alexander L. N.
Abstract: Wastewater‐based epidemiology (WBE) is based on the analysis of human metabolic excretion products (biomarkers) of xenobiotics in wastewater, to gain information about various lifestyles and health aspects of a population in an evidence‐based manner. Due to the complex wastewater matrix and trace level occurrence of human biomarkers in the sewage network, it is crucial to have sensitive analytical procedures available. Additionally, to improve the value of WBE as a complementary epidemiological source, there is increasing pressure on the analysis of more compounds, more locations and more samples. A high‐throughput method based on 96‐well Oasis MCX solid‐phase extraction (SPE), requiring less influent wastewater (2 mL), was developed in accordance with the European Medicines Agency guidelines. Validation was successful for 28 parent drugs and metabolites of antidepressants, opioids and drugs of abuse. The selection of biomarkers and quantification limit was chosen to be relevant for WBE and was predominantly 10 ng/L or below. The final method was successfully applied to 24‐h composite samples of October 2019 ( n  = 27), obtained from an urban wastewater treatment plant in Leuven (Belgium). Abstract :